DAMPAK TRADISI PACU JALUR TERHADAP KEHIDUPAN MASYARAKAT DI KECAMATAN KUANTAN HILIR - Dedianto "; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Positive impact means good and pleasant things that bring progress. While negative impact means unpleasant things that bring difficulties, anxiety, and harm among people. Positive impact of PacuJalur Tradition in RantauKuantan brings progress for people, especially in science field. Some of negative impacts are: people become materialist, egoistic, and individualist, yet these negative impact do not influence the life of people in two villages in RantauKuantan.The purpose of this research is to find out the impact of PacuJalur Tradition to the life of people in two villages in RantauKuantankecamatanKuantanHilir. Especially in social science, the change of value and attitude. This is a Descriptive Naturalistic with qualitative approach. Subject and sample of this research is figures in society in two villages. There are 8 people of them. The subject and sample become key sample. To collect the data, writer do interview.Data is exposed based on respondents opinion. Result shows that positive impact of the tradition are to bring up the habit of “gotongroyong”, “silaturrahmi”, self confidence and tradition perpetuation. The negative impact of this tradition are people don’t want to involve in “gotongroyong”, lack of solidarity, small amount of people, assume themselves super and individualist. Education, training, and culture adaptation are improved. The negative impact can be seen from foreign culture imitation and the change of “paguyuban” culture. Generally, the impact of PacuJalur Tradition to the life of people in two villages in RantauKuantan is categorized into positive impact, while the negative impact does not influence the life of people.Keyword: impact, (pacujalur tradition to the life of people)